Le paysage sonore comme révélateur de l’esprit du lieu : une sécrétion latente - Mohsen Ben Hadj Salem; Chiraz Chtara (VertigO)
The sound atmosphere determines all our urban experience. Today, it is impossible to ignore it or to consider it only like discomfort. What is the role of the soundscape in the creation of a sensitive, shared, historical and contemporary heritage? How to introduce sound qualities in the urban heritage problem? Visual landscapes change over time and our aesthetic categories make them appreciate differently, the daily soundscapes have also changed. The medina of Tunis is a revealing example of the sedimentation of the soundscapes. Our hypothesis is that the medina soundscape is a real device of social interactions that involves singular sound-perception processes. The objective of this contribution is to open the way to the historic soundscape, with a different relationship to the past. This historical exploration aims to identify the elements that deserve our attention in the sensitive landscape and that could guide the urban and architectural design. In other words, it’s a question of revealing the auditory identity values of the places in order to propose global intentions. If we know how to define visual landscape charters, we know much less to design their sonic tone. The role of the sonic dimension, even the full participation of this sensitive modality in the constitution of a heritage is the essential topic of this work.